The Variability of Puroindoline-Encoding Alleles and Their Influence on Grain Hardness in Modern Wheat Cultivars Cultivated in Poland, Breeding Lines and Polish Old Landraces (Triticum aestivum L.) - Mateusz Przyborowski; Sebastian Gasparis; Maciej Kała; Wacław Orczyk; Anna Nadolska-Orczyk (Agronomy, 2020)
Wheat (Triticum aestivum L.) grain hardness is determined mainly by variations in puroindoline genes (Pina-D1 and Pinb-D1), which are located on the short arm of chromosome 5D. This trait has a direct effect on the technological properties of the flour and the final product quality. The objective of the study was to analyze the mutation frequency in both Pin genes and their influence on grain hardness in 118 modern bread wheat cultivars and breeding lines cultivated in Poland, and 80 landraces from Poland. The PCR products containing the Pin gene coding sequences were sequenced by the Sanger method. Based on detected the SNPs (single-nucleotide polymorphisms) we designed CAPS (cleaved amplified polymorphic sequence) markers for the fast screening of Pinb alleles in a large number of genotypes. All analyzed cultivars, breeding lines, and landraces possess the wild-type Pina-D1a allele. Allelic variation was observed within the Pinb gene. The most frequently occurring allele in modern wheat cultivars and breeding lines (over 50%) was Pinb-D1b. The contribution of the remaining alleles (Pinb-D1a, Pinb-D1c, and Pinb-D1d) was much less (approx. 15% each). In landraces, the most frequent allele was Pinb-D1a (over 70%), followed by Pinb-D1b (21% frequency). Pinb-D1c and Pinb-D1g were found in individual varieties. SKCS (single-kernel characterization system) analysis revealed that grain hardness was strictly connected with Pinb gene allelic variation in most tested cultivars. The mean grain hardness values were significantly greater in cultivars with mutant Pinb variants as compared to those with the wild-type Pinb-D1a allele. Based on grain hardness measured by SKCS, we classified the analyzed cultivars and lines into different classes according to a previously proposed classification system.